2000
DOI: 10.1046/j.1365-2095.2000.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of pancreatic enzymes in larval red drumSciaenops ocellatus

Abstract: The growth, survival and trypsin, lipase and amylase activities of red drum larvae were measured in two experiments. For the first trial, a group was fed live prey only (L) and another group was fed a combination of a microparticulate diet (MPD) and live food (L‐MP). For the second growth trial a group fed the MPD only (MP) and a starvation group (ST) were examined in addition to the L and L‐MP treatments. Enzyme activities of live prey were measured to estimate their possible contribution to larval digestion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 21 publications
9
69
0
5
Order By: Relevance
“…Also, similar profile for amylase was recorded by Gisbert et al (2009) that they reported similarly two peak steps which have been measured firstly around 2 DAH concurrently with hatching and starting of exogenous feeding and also secondly after 25 DAH for this species . Additionally, these information were parallel with results obtained from D. labrax (Zambonino Infante and Cahu, 1994), S. ocellatus (Lazo et al, 2000), large yellow croaker, Pseudosciaena crocea, (Ma et al, 2005), and P. erythrinus (Suzer et al, 2006b) larvae. Additionally, Pérez-Jiménez et al estimated that dietary carbohydrate content seems to induce changes in protease, amylase and lipase activity even though the authors conducted feeding experiments in juvenile of Dentex dentex at 91.7±1.4 g mean mass (Pérez-Jiménez et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Also, similar profile for amylase was recorded by Gisbert et al (2009) that they reported similarly two peak steps which have been measured firstly around 2 DAH concurrently with hatching and starting of exogenous feeding and also secondly after 25 DAH for this species . Additionally, these information were parallel with results obtained from D. labrax (Zambonino Infante and Cahu, 1994), S. ocellatus (Lazo et al, 2000), large yellow croaker, Pseudosciaena crocea, (Ma et al, 2005), and P. erythrinus (Suzer et al, 2006b) larvae. Additionally, Pérez-Jiménez et al estimated that dietary carbohydrate content seems to induce changes in protease, amylase and lipase activity even though the authors conducted feeding experiments in juvenile of Dentex dentex at 91.7±1.4 g mean mass (Pérez-Jiménez et al, 2009).…”
Section: Discussionsupporting
confidence: 66%
“…As observed for trypsin, chymotrypsin was first detected in preflexion stage on day 3 (concurrently with mouth opening) and its specific activity strongly correlated with tryptic activity of D. dentex larvae. Besides, chymotrypsin was first detected concurrently with trypsin at the day of mouth opening in the cultured marine fish S. aurata after 3 DAH (Moyano et al, 1996), P. eryhtrinus after 3 DAH (Suzer et al, 2006b), P. pagrus after 3 DAH (Suzer et al, 2007a), S. senegalensis after 2 DAH (Martinez et al, 1999), S. ocellatus after 3 DAH (Lazo et al, 2000), and D. labrax after 5 DAH (Zambonino Infante and Cahu, 1994). However, similarly to trypsin, chymotryptic activity exponentially increased by larval size and age during the first month and then gradually decreased until end of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Daily mortalities of darkbarbel catfish larvae (daily dead larvae/initial number of larvae, mean per treatment) during development. red drum (Lazo et al, 2000), while at 2 DAH (first feeding) in the brush border and cytoplasm of enterocytes of Senegalese sole (Ribeiro et al, 1999). The presence of enzymatic capacity before first feeding suggests that these enzymes were induced by genetic control, not by food intake.…”
Section: Tablementioning
confidence: 98%